THE ASSOCIATION OF FAMILY SUPPORT IN FULFILLING HEALTHY NUTRITIOUS FOODS, PROTEIN AND MICRONUTRIENT INTAKE WITH HEMOGLOBIN LEVELS AMONG ELDERLY - Luberta Ebta Wiyani; Diffah Hanim; Dono Indarto (Media Gizi Indonesia, 2021)
The elderly usually accompanied by many impairments due to decline in organ functioning which have a great impact on their daily intake and leads to anemia. Many elderlies also have mobility impairment which make them become more dependent and need supports from their family. The aim of this study is to investigate the relationship of family support, the daily intake of protein, iron, vitamin C with hemoglobin levels in elderly. This observational analytic study with cross-sectional design was performed in 185 elderlies aged 60-79 years determined using the OpenEpi program. Subjects collected by simple random sampling from chosen Posyandu in Klaten and Sragen districts. The data on daily intake and family support in fulﬁlling healthy nutritious foods were collected by using a 2x24-hour food recall form and a modiﬁed questionnaire from Hanim’s study. Hemoglobin levels were measured from venous blood using Cyanmethhemoglobin method. The data were analyzed using the Pearson test and Multiple Linear Regression test. The prevalence of mild anemia was found in 10.27% women and 5.41% men. Family support (b=0.09, 95%CI:0.003- 0.18), protein intake (b=0.41, 95%CI:0.25-0.57), iron intake (b=0.19, 95%CI:0.96-0.29), vitamin C intake (b=0.10, 95%CI:0.02-0.41) were signiﬁcantly associated with hemoglobin levels (p<0.05). To conclude, suﬃcient family support, adequate intake of protein, iron and vitamin C are associated to higher hemoglobin levels.